Islam Obscured - Timothy P. Daniels (International Institute of Islamic Thought, 2008)
Daniel Martin Varisco’s Islam Obscured: The Rhetoric of Anthropological Representation provides a very sound and well-informed literary critique of Clifford Geertz’s Islam Observed (1968), Ernest Gellner’s Muslim Society (1981), Fatima Mernissi’s Beyond the Veil (1975), and Akbar Ahmed’s Discovering Islam (1988). The author, an experienced ethnographer of Middle Eastern societies, examines the treatments and representations of Islam in these seminal texts. After presenting his topic and background in the introduction, he demonstrates how these four authors obscured, misrepresented, and elided the everyday lives of Muslims. In the epilogue, Varisco gleans some important lessons for the study of Islam from his entertaining and witty exploration of these social science texts. In the book’s introduction, the author briefly discusses the intellectual history of anthropology and ethnographic studies of Muslims. He notes that the discipline of anthropology has encountered numerous problems, including its recognition of Victorian traveler’s reports, Spencerian “evolutionism,” and the postcolonial critique of Eurocentric textual representations of non-western others. Addressing the current state of anthropological theory, Varisco mentions the blurring of boundaries between established disciplines as well as the particularly American problem over whether to maintain the four-field approach of holistically studying human beings. In keeping with this Eurocentric slant toward “primitives,” he observes that there were very few ethnographic studies of Muslims, except Evans- Pritchard’s 1940s work on Cyrenaican Bedouins and those by others following his example, until ethnographers began to produce Robert Redfieldinfluenced community studies.Yetmany of these latter studies were done by researchers who, with little proficiency inArabic, wrote from a distance and thus barely penetrated the surface of Islam in local Muslims’ lives. Varisco ...